Application of pi Circuits for Simulation of Corona Effect in Transmission Lines - Lessa, L. S. [UNESP]; Prado, A. J. [UNESP]; Bonelli, M. L. [UNESP]; Kurokawa, S. [UNESP]; Pissolato Filho, J.; Bovolato, L. F. [UNESP] (IEEE, 2012)
In this article, it is represented by state variables phase a transmission line which parameters are considered frequency independently and frequency dependent. Based on previous analyses, it is used the reasonable number of p circuits and the number of blocks composed by parallel resistor and inductor for reduction of numerical oscillations. It is analyzed the influence of the increase of the RL parallel blocks in the obtained results. The RL parallel blocks are used for inclusion of the frequency influence in the transmission line longitudinal parameter. It is a simple model that is been used by undergraduate students for simulation of traveling wave phenomena in transmission lines. Considering the model without frequency influence, it is included a representation of the corona effect. Some simulations are carried considering the corona effect and they are compared to the results without this phenomenon.
Keywords: Electromagnetic transient; EMTP; mathematical model; simulation; transmission lines; pi circuit; numeric method; wave traveling